Expression and purification of recombinant coat protein of sugarcane mosaic virus from Indonesian isolate as an antigen for antibody production - Natalia Tri Astuti; Nurmalasari Darsono; Suvia Widyaningrum; Widhi Dyah Sawitri; Sri Puji Astuti; Win Darmanto (Universitas Gadjah Mada, 2019)
Sugarcane mosaic virus (SCMV, genus Potyvirus, family Potyviridae) is a prominent pathogen of sugarcane (Saccharum sp. hybrids). It can cause losses in susceptible varieties, in crop as well as sugar production, economically. Although it has been studied in major sugar-producing countries, research on the definement of SCMV from Indonesian isolates based on molecular study has been very limited. This study aimed to obtain a proper recombinant antigens emanating from coat protein of SCMV from Indonesian isolate in order to produce polyclonal antibodies that cann be used for immunodiagnosis assays in a subsequent study. A gene-encoding coat protein of SCMV (CP-SCMV) was amplified using RT-PCR and cloned into vector pJET1.2. The cDNA was inserted into 6X His-tag expression plasmid of pET28a(+) and over-expressed in Escherichia coli BL21(DE3) to produce a recombinant protein. The highest expression was found in 0.1M IPTG induction media for 5 h at 37oC. SDS-PAGE analysis clarified that the recombinant CP-SCMV remained as an insoluble fraction. Purifications was carried out by the affinity Ni-NTA resin, followed by electroelution to obtain a highly purified protein. To meet the quality requirements of a proper antigen, the highly purified protein was concentrated. A molecular weight of the rCP-SCMV (approximately 40 kDa) was clearly observed by 10% SDS-PAGE at the concentration of 16.184 mg/mL.